PENGARUH PENAMBAHAN UREA, KOMPOS CAIR, DAN CAMPURAN KOMPOS DENGAN GULA TERHADAP KANDUNGAN BOD DAN COD PADA PENGOLAHAN AIR LIMBAH PENCELUPAN - I W. BUDIARSA SUYASA; WAHYU DWIJANI (Master Program of Environmental Science, Postgraduate Program of Udayana University)
Seed of Mikroorganisme from river mud sediment that sampling of Tebe counted ± 10 gr. Phase of seeding withcapasity of 3 litre (sediment) of Tebe, was counted by 3 gr, NPK = 2,5 gr, Mgso4.7H2O = 0,2 gr, and aquades untilborder. Aerasi is conducted by using given aerator into seed place. Growth of microorganism was measured of eachevery 2 day during one week with measuring value of biomass till reach price 2000 mg / L. After seed process, intotreatment place aeraeration of process of seeding domestic waste water and each counted 500 mL. Variation of nutrienttreatment (NPK) respectely 0,25 gr, 0,50 gr, 0,75 gr and 1.00 gr while control without addition of nutrient. Process ismeasured by value of pH, COD on 1, 3, 5, and 7 day.Result of research show that Sediment River of Tebe have potency as active mud. This matter is showed withgrowth of biomass of microbe till reach number 3.610 mg / L. Addition variation of NPK at treat of domestic waste havean effect on very real to value of COD. Best Result with value of COD lowest that is 38,096 mg / L with its effectivenessto 91,11% at addition of NPK counted 0,5 gr.